Comparative study for CT-guided (125)I seed implantation assisted by 3D printing coplanar and non-coplanar template in peripheral lung cancer - Ji, Zhe (J Contemp Brachytherapy, 2019)
PURPOSE: We compared the three-dimensional printed non-coplanar template (3DPNCT) plans with 3D-printed coplanar template (3DPCT) plans for radioactive seed implantation (RSI) in lung cancer and explored the differences between the two technologies. MATERIAL AND METHODS: 33 patients with peripheral lung cancer that received 3DPCT-assisted RSI in our department between June 2017 and February 2018 were analyzed. A 3DPNCT plan was re-designed for all patients. The prescribed dose and seed activity in the new plan were the same as the 3DPCT plan. The data in the two plans were compared, including seed number, needle number, number of needles needed to cross the ribs, and dosimetry parameters. Dosimetry parameters included D(90), D(mean), MPD (minimum peripheral dose), V(100), V(150), CI (conformity index), EI (external index), HI (homogeneity index) of target volume, D(2cc) of spinal cord and aorta, and V(20) of affected side lung. We used a paired t-test and two groups of related non-parameters tests to examine statistical significance. A p value < 0.05 was considered statistically significant. RESULTS: We found no significant difference in dosimetry parameters (p > 0.05), except MPD. The mean MPD of the 3DPNCT plan was significantly higher than the 3DPCT plan (88.5 Gy and 81.8 Gy, respectively, p = 0.017). The number of needles used in the 3DPNCT plan and the number of needles needed to cross the ribs were significantly less compared with the 3DPCT plan (p = 0.000). CONCLUSIONS: The dose distributions of the two 3DPCT plans were similar. 3DPNCT plan had a higher dose in target volume margin, with fewer needles and fewer breaks to the ribs.